DAYA SAING JAGUNG DI KECAMATAN SEKAMPUNG UDIK KABUPATEN LAMPUNG TIMUR - Cahya Indah Franiawati; Wan Abbas Zakaria; Umi Kalsum (Lampung University, 2013)
This research aims to analyze the competitiveness of corn and the effect of input-output price changes on the competitiveness of corn farming in Sekampung Udik District, East Lampung Regency. This research was held in Sidorejo Village, Sekampung Udik District, East Lampung Regency. The respondents of this research were 6 farmers implementing intensive farming management, taken using purposive sampling. The competitiveness was analyzed using PAM (Policy Analysis Matrix). The results showed that corn farming in Sekampung Udik District, East Lampung Regency was competitive (PCR = 0.3499 and DRC = 0.2944). The decreasing of corn price by 26%, the increasing of fertilizer price (urea = 33.33%, SP-36 = 29.03%, Phonska = 31.43%, and KCl = 25%), the increasing of seed price and landrate by 4.28%, caused a decrease in the competitiveness of corn farming. The competitiveness of corn farming in Sekampung Udik District, East Lampung Regency was sensitive to the decreasing of corn price by 26%.Key words: competitiveness, corn, PAM, sensitivity